Ovarian sarcomas: a review of literature - S. A. Shvachko; A. N. Gritsai; N. I. Lazareva; S. B. Peterson; A. V. Vasilevskaya (Опухоли женской репродуктивной системы, 2014)
The review describes the etiology and clinical features of ovarian sarcomas and current approaches applied to their diagnosis and treatment.